New insights from monogenic diabetes for “common” type 2 diabetes - TALLAPRAGADA, DIVYA SRI PRIYANKA; BHASKAR, SEEMA; CHANDAK, GIRIRAJ RATAN (Frontiers in Genetics, 2015)
Boundaries between monogenic and complex genetic diseases are becoming increasingly blurred, as a result of better understanding of phenotypes and their genetic determinants. This has made a large impact on the way complex disease genetics is now been investigated. Starting from conventional approaches like familial linkage, positional cloning and candidate genes strategies typically used for monogenic diseases, the scope of complex disease genetics has grown exponentially with scientific and technological advances in recent times. However, despite identification of multiple loci harboring common and rare variants in complex diseases, interpreting and evaluating their functional role has proven to be difficult and information from monogenic disease, especially related to the intermediate traits associated with disease comes handy. The significant overlap between these traits and phenotypes of monogenic diseases with related complex disease provides a platform to understand the disease biology better. In this review, we would discuss about one such complex disease, type 2 diabetes, which shares marked similarity of intermediate traits with different forms of monogenic diabetes.